How Do Leaders Build Organizational Resilience? An Empirical Literature Review - Choirum Rindah Istiqaroh; Indrianawati Usman; Dhyah Harjanti (Universitas Airlangga, 2022)
Objective: The purpose of this study is to compile a synthesis of the application of leadership in building organizational resilience, especially when the organization faces a crisis or difficulty. Design/Methods/Approach: The approach used is a literature review, with a systematic search from a database of scientific journals indexed by SCOPUS as an indexing organization for reputable research journals. Selected journals that match the theme will be reviewed and data synthesized. Findings: When the organization is down, leaders play various roles in building organizational resilience. The leader develops and disseminates the organization's vision, builds awareness, ensures the learning process runs, builds capability and adaptability, strengthens physiological capital, and builds an organizational culture and team resilience. These roles are doable by implementing the right leadership style and strategy, configuring resources, and building relationships and collaborations. Furthermore, this research also identified the stages of the process and their mechanisms. From the results of this study, there are several opportunities for future research. Originality: This research generates a literature review on building organizational resilience with a leadership perspective and its synthesis model. Practical/Policy implication (optional): This research provides a more comprehensive understanding of how resilience is fostered in organizations and best practices regarding the role of leaders in building organizational resilience.